2014
DOI: 10.1111/clr.12396
|View full text |Cite
|
Sign up to set email alerts
|

Anorganic bovine bone (ABB) vs. autologous bone (AB) plus ABB in maxillary sinus grafting. A prospective non‐randomized clinical and histomorphometrical trial

Abstract: The usage of ABB plus AB to a 1/1 ratio leads to an amount of newly formed bone comparable with the solitary use of ABB after grafting of the maxillary sinus. Considering that ABB is a non-resorbable bone substitute, it can be hypothesized that this leads to stable bone over time and long-term implant success. Importantly, in the sole use of ABB, bone grafting and therefore donor site morbidities can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 37 publications
6
73
1
3
Order By: Relevance
“…36 Some studies reported limited volumetric graft changes after augmentation with different mixtures of bovine bone mineral and autologous bone. 32,33 Therefore, according to the current study results, although no significant differences found between xenograft and xenograft þ PTG groups, the permanent nonresorbable and porous properties of PTG may have beneficial effect on graft volume preservation and associated long-term implant success.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…36 Some studies reported limited volumetric graft changes after augmentation with different mixtures of bovine bone mineral and autologous bone. 32,33 Therefore, according to the current study results, although no significant differences found between xenograft and xenograft þ PTG groups, the permanent nonresorbable and porous properties of PTG may have beneficial effect on graft volume preservation and associated long-term implant success.…”
Section: Discussionsupporting
confidence: 47%
“…Different outcomes among studies may be because of different measuring methods, methodological factors, healing times, the ratio of the used mixtures, the ratio of used autologous bone, particle sizes of the bone substitute material, patient characteristics, and how dense the filler is packed into the cavity of the maxillary sinus. 33 The higher NB percentages in the current study may be because of the long time (mean 8.5 months) between grafting and biopsy procedure. 34 Another factor may be the use of barrier membrane to cover the lateral sinus oseteotomy in all cases that has been proved to promote better healing.…”
Section: Discussionmentioning
confidence: 56%
“…These biomaterials provide both mechanical support and osteoinductive/osteoconductive activity to regenerating bone tissues. 18 The conclusions were controversial: no great advantage regarding bone healing was observed [6][7][8]11,14 ; some researchers even claimed that the higher the proportion of AB, the lower the outcome augmentation volume. Deproteinized bovine bone mineral (DBBM; Bio-Oss, Geistlich Pharma, Wolhusen, Switzerland) has good biocompatibility and osteoconductivity, which are favorable features of bone substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Various approaches have been tried to minimize the required graft and maximize its healing and integration potentials. [4][5][6] Since the introduction of plateletrich plasma (PRP) by Marx et al 7 as an autologous source of growth factors, it has gained increasing interest by clinicians and researchers. A number of experimental and clinical studies have been developed to investigate various aspects of the possible healing enhancement provided.…”
mentioning
confidence: 99%